Straightforward and Controlled Shape Access to Efficient Macrocyclic Imidazolylboronium Anion Receptors. Issue 26 (24th May 2016) - Toure, Momar; Charles, Laurence; Chendo, Christophe; Viel, Stéphane; Chuzel, Olivier; Parrain, Jean‐Luc
Abstract: A straightforward synthesis of air‐ and water‐stable bis‐cationic macrocyclic imidazolylboronium anion receptors is described herein. By taking advantage of the bulky and rigid 9‐borabicyclo[3.3.1]‐nonane (9‐BBN) attaching point and a well‐designed bis‐imidazolylaryl, highly stable dimeric imidazolylboronium macrocycles were synthesized. Additionally, NMR spectroscopy ( 1 H, DOSY, and HOESY), mass spectrometry (MS), and X‐ray diffraction studies revealed that these macrocyclic scaffolds can bind several monoanions with high association constants in DMSO, and are particularly sensitive for the MS detection of anions (with concentrations in the nm range). This anion/receptor interaction involves eight C−H binding sites, which include C sp 2 −H and unusual Csp3 −H hydrogen‐bonding donors. Abstract : Plus to see minus : A straightforward and efficient synthesis of highly effective bis‐cationic macrocyclic imidazolylboronium anion receptors (see figure) is depicted in this study. The crucial boronium part governed the self‐assembly and the specific electronic property of this novel anion receptor. The bis‐cationic nature of the macrocycle allowed trapped anions to be detected directly by using positive mass spectrometry.